India - Ladiankalan village - Punjab - CGIAR Research Program on Climate Change, Agriculture and Food Security (2011)
Farmers talk about the changes in the weather and how they are trying to adapt. They have had to switch to hybrid seeds that require less pesticides and water, but still produce higher yields. Growing poplar trees to complement the agriculture production is also being considered. Poplar trees need less water than other trees and grow to full size within four years, making it an additional income without affecting rice yields.